City Branding Strategy, in Order to Show the City of Batu as a Tourist Destination in Indonesia - PANJAITAN, Hotman (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020, 2020)
This research was conducted to obtain a clear relationship between the strategy of city branding in increasing tourist visits to the city of Batu Indonesai. The researcher proposes a new model and wants to explain the concept of a new indicator on the brand value destination variable. From the results of testing the model, using structural equation modeling (SEM) analysis, convenience sampling method and with the help of PLS Warp software, on 270 respondents. The results showed that the research model was accepted. The proposed model shows destination brand value to be the main determinant of tourist satisfaction and loyalty. The model can also prove that the indicators, comfort, fairness of costs, fun, get benefits make a positive contribution to the destination brand value. Where this is a new thing proposed in this study. The practical implication of the research is that tourism managers should pay attention to and enhance brand image, which until now has not yet had a maximum impact on destination brand value, by building brand popularity, building competitive advantages that can be used as an excuse for tourists to visit tourist objects